Age-related perceptions of facial profile attractiveness in South Africans - Morar, Ajay (My University, 2010)
This study evaluated the influence of age on the perception of facial attractiveness in three samples of South Africans. Eight digitally morphed lateral facial profiles were created by means of computer animation software and presented, in sequential order, to 1798 school learners, 694 university students and 323 school teachers. Each participant was asked to complete a questionnaire in addition to choosing a single face he/she perceived to be the most attractive. Statistical tests included frequency distributions, percentages, cross-tabulations, odds ratios and the Pearson Chi-square test. Results demonstrated that age was a factor in the perception of facial attractiveness particularly amongst individuals of school-going age. Thereafter, increasing age did not exert a significant influence on the perception of profile preference. There was a definite trend towards the preference for less protrusive facial profiles. Nevertheless, due consideration should be given to the individuality associated with aesthetic choices as a significant proportion of raters did indicate a preference for profiles exhibiting mild protrusion. Furthermore, race and cultural background do appear to play a significant role in the perception of facial profile preferences. It is suggested that future studies of a similar nature be undertaken in order to provide the data to permit comparison with the results reported in this study.
MSc (Dent), Orthodontics, Faculty of Health Sciences, University of the Witwatersrand
Keywords: facial profiles; preferences; South Africans